Synthesis of PbS nanocrystallites using a novel single molecule precursors approach: X-ray single-crystal structure of Pb(S2CNEtPri)2 - Trindade, Tito (2012)
The synthesis and characterisation of some lead(II) dithiocarbamato complexes Pb(S2CNRR¾)2 is reported. These compounds were used as single molecule precursors to produce nanocrystalline PbS by their thermolysis in trioctylphosphine oxide. The optical and morphological properties of the resulting PbS nanocrystallites were investigated; the influence of experimental parameters, such as precursor, growth time and temperature, on the final nanodispersed materials is also reported.